Implementasi Algoritma Merkle-Hellman Knapsack dalam Penyandian Record Database - Rahmadani, Reni; Hutahaean, Harvei Desmon; Sari, Ressy Dwitias (LPPM UNIKA Santo Thomas Medan, 2020)
A lot of data is misused without the data owner being aware of it. Software developers must ensure the security user data on their system. Due to the size of the market that houses data, the security of record databases must be of great concern. Cryptographic systems or data encryption can be used for data security. The Merkle-Hellman Knapsack algorithm is included in public-key cryptography because it uses different keys for the encryption and decryption processes. This algorithm belongs to the NP-complete algorithm which cannot be solved in polynomial order time. This algorithm has stages of key generation, encryption, and decryption. The results of this study secure database records from theft by storing records in the form of ciphertext/password. Ciphertext generated by algorithmic encryption has a larger size than plaintext.